2021
DOI: 10.1177/0020294021997494
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical classification method of electricity consumption industries through TNPE and Bayes

Abstract: As the multi-daily electricity consumption behaviors have the strong characteristics of dynamicity, nonlinearity and locality caused by temporal manifold structure, the existing methods are difficult to fine-grained and accurately classify it. To solve this problem, this paper proposes a hierarchical classification method based on the temporal extension of the neighborhood preserving embedding algorithm (TNPE) and Bayes. The input data are multi daily-load curves of a single consumer, including power-hour-day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The NPE algorithm, serving as a linear approximation of local linear embedding , is employed for dimensionality reduction [20,21]. Notably, recent studies have emerged focusing on enhancing the NPE algorithm, offering fresh insights and inspirations for further developments in this area [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The NPE algorithm, serving as a linear approximation of local linear embedding , is employed for dimensionality reduction [20,21]. Notably, recent studies have emerged focusing on enhancing the NPE algorithm, offering fresh insights and inspirations for further developments in this area [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The literature [15] analyzed the information transfer routes of electricity consumption data based on transfer entropy and minimum spanning tree model and found that the transfer entropy of electricity information in Guangdong Province was lower than that in other provinces in China. The literature [16] proposed a hierarchical classification algorithm of the Bayesian algorithm to evaluate and analyze the electricity consumption information of electricity consumption industries and identified the characteristics of the electricity load in different industries through TNPE to achieve the attribution analysis of electricity consumption. The literature [17] identifies power theft and associated users through statistical information on electricity consumption to maintain the stability and normal operation of the power grid.…”
Section: Introductionmentioning
confidence: 99%